"Take Heede When Ye Wash": Recognizing the Labor of Enslaved Laundresses on Southern Plantations. (4th May 2022) - McIlvoy, Karen E.
ABSTRACT: Laundry represented a significant portion of the domestic labor on nineteenth century plantations. However, despite the ubiquity of their task, enslaved African American washerwomen have been neglected in the historical study of plantation labor. By situating archaeological interpretations of enslaved labor within the historical context of laundry, archaeologists can better incorporate this oft-overlooked chore into interpretations of female labor on Southern plantations. Using this technique, this article explores laundering at Poplar Forest, Thomas Jefferson's retreat home and plantation in central Virginia.